An Investigation Link between Critical Thinking and Reading Comprehension: A case of A Madrasah in Lubuk Linggau, South Sumatera - HADY MARESYAH PUTRA (Ta'dib: Jurnal Pendidikan Islam, 2019)
The aims of the study were to find out (1) whether critical thinking had any significant correlation to reading comprehension of English Education Study Program Students at one of Madrasahs in Lubuk Linggau, South Sumatera; and (2) whether critical thinking significantly influenced their reading comprehension. The study was in the form of correlational research method. The population of the study was 636 active EFL students. By using purposive sampling technique, there were 108 students involved as participants in this research. The instruments, both critical thinking test and reading comprehension test, were analyzed in order to gain the data of the study. To find out whether critical thinking of students, as a whole, had any correlation with students' reading comprehension achievement or not, Pearson-Product Moment Correlation Coefficient was applied. Besides, to answer the second research problem, to find the significant influence of critical thinking, the coefficient determination (R Square) was applied. From the data analysis, it was found that there was significant correlation between students’ critical thinking and their reading comprehension since the p-value was (0.020) was less than significance value (0.020 < 0.005). In addition, to know the percentage of critical thinking skill influence on reading comprehension, R-square was obtained. The students’ critical thinking skill gave significant effect with 48.4% contribution towards reading comprehension. In short, critical thinking had relation to reading comprehension of the students of one of Madrasahs in Lubuk Linggau, South Sumatera.